δ18O VALUES OF MUDROCKS: MORE EVIDENCE FOR AN 18O-BUFFERED OCEAN - Land L.S.; Lynch F.L. (My University, 1996)
The whole-rock δ18O of mudrocks, as well as the δ18O of the clay-sized silicate fraction, does not change in any systematic manner over Paleozoic and late Proterozoic time. Therefore, the δ18O of the ocean has not changed (except a per mil or so as the result of glaciation/deglaciation) over the last billion years of Earth history.
Keywords: Proterozoic; Paleozoic; Precambrian::Proterozoic; Докембрий::Протерозой; Paleozoic; Палеозой